EDUKASI PENGETAHUAN SWAMEDIKASI PENYAKIT KULIT SEBAGAI UPAYA UNTUK MENINGKATKAN KESEHATAN DI LINGKUNGAN PANTI ASUHAN WILAYAH KARTASURA - Yulianti, Tri; Imanni, Berlian Fathimata; Findari, Ferdina Wahyu; Prabasakti, Radin Mundingwangi Nurangga; Meylani, Erlina Aisyah; Adhisa, Zusita Geby Candra (LPPM Institut Pendidikan Nusantara Global, 2024)
Skin is the outer layer of the human body that is directly adjacent to the environment and has a function as protection from several pathogens such as bacteria, fungi, and viruses and functions in defense. One of the problems that can arise even though the manifestation is not severe is skin disease. If skin diseases are not treated properly, they can become chronic diseases that are very disturbing to health. This community service aims to increase knowledge about self-medication of skin diseases in the environment of Santri Wisma Asuhan Yatim Nurul Huda Kartasura. This community service consists of activity survey stages, licensing, preparation, implementation and evaluation of activities. There is a pretest and posttest to measure the ability of students to knowledge of self-medication of skin diseases. Then a quantitative analysis was carried out which included a data normality test and a t-test for pretest and posttest. The results of community service showed that there were 33 students who participated in community service activities. With most participants having a high school education and all students have never received education about skin diseases. The average knowledge of students for pretest scores is 64.03 ± 13.04, while the average posttest score is 81.61 ± 7.99. There is a significant difference in pretest and posttest knowledge (p = 0.000).